Multifunctional biodegradable lube oil additives: Synthesis, characterization, and performance evaluation. (2nd January 2017) - Ghosh, P.; Dey, K.; Upadhyay, M.; Das, T.
ABSTRACT: Copolymers of different concentration of decyl acrylate and 1-decene with rice bran oil were prepared and their characterization was carried out by spectral (NMR, IR), thermogravimetric, and gel permeation chromatography analysis. Performance evaluation of them in lube oil indicates that the polymers effectively act as pour point depressant and viscosity modifier. The viscosity index and pour point values depend on the nature of mineral base oils, polymer type, and also on the concentration of the additives in solution. Biodegradability test was also carried out and as anticipated, the rice bran oil–copolymers showed excellent biodegradable nature among the additives.